Enhancing proton conductivity of proton exchange membrane with SPES nanofibers containing porous organic cage. (28th February 2020) - Xu, Xianlin; Shao, Zhufeng; Shi, Lei; Cheng, Bowen; Yin, Xuan; Zhuang, Xupin; Di, Youbo
Abstract: Effective proton conducting sites and establishing proton channels are two critical factors in developing high‐performance proton exchange membranes. This study first establishes a strategy in designing effective proton conducting channels for Nafion by using solution blowing of sulfonated polyethersulfone (SPES) nanofibers containing CC3, which is an emerging porous organic cage that possesses the advantages of dissolvable organic solvents and high proton conduction from its interconnected three‐dimensional pore structure. Our strategy results in SPES nanofiber networks with CC3 uniformly involved in and composite membranes with Nafion‐filled interfiber voids. Benefiting from such structural features, the composite membrane exhibits high proton conductivity (0.315 S cm −1 at 80°C and 100% RH), low methanol permeability (0.69 × 10 −7 cm 2 S −1 ), excellent water absorption, thermal and dimensional stability, and single‐cell performance. This study provides not only a valuable reference for the application of CC3 but also a new idea for establishment of proton transfer channels.